2018
DOI: 10.1002/ijc.31790
|View full text |Cite
|
Sign up to set email alerts
|

Acidic extracellular environment affects miRNA expression in tumors in vitro and in vivo

Abstract: Hypoxia can control the expression of miRNAs in tumors which play an important role for the control of the malignant behavior. The aim of the study was to analyze whether extracellular acidosis, a common feature of tumors, also has an impact on the miRNA expression in isolated cells as well as in solid tumors. MiRNA expression was analyzed in two rat tumor cell lines (AT1 prostate and Walker-256 mammary carcinomas) by NGS and qPCR. In vivo the same cell lines were implanted subcutaneously and the tumor pH was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
(113 reference statements)
1
12
0
Order By: Relevance
“…According to other authors [72], miRNAs expressed in isolated tumor cells growing in vitro only partially correspond to those expressed in tumors growing in animals. Indeed, in vivo, miRNAs are influenced by external stimuli in the tumor microenvironment such as the acidic extracellular environment, the presence of hormones [73] or cytokines [74], external physical stimuli [75] or hypoxia [76].…”
Section: Discussionmentioning
confidence: 99%
“…According to other authors [72], miRNAs expressed in isolated tumor cells growing in vitro only partially correspond to those expressed in tumors growing in animals. Indeed, in vivo, miRNAs are influenced by external stimuli in the tumor microenvironment such as the acidic extracellular environment, the presence of hormones [73] or cytokines [74], external physical stimuli [75] or hypoxia [76].…”
Section: Discussionmentioning
confidence: 99%
“…As cancer progresses, heterogeneous subpopulations of cancer cells arise with different phenotypic [ 66 ] and molecular signatures [ 67 ]. Transcriptional heterogeneity in tumors can arise as a response to environmental conditions including pH [ 68 ]. Importantly, transcriptional heterogeneity can confer an array of fitness advantages to individual cells that contribute to a higher likelihood of cancer cell proliferation, survival, metastasis, or therapy resistance [ 64 , 69 ].…”
Section: Heterogeneity and Phimentioning
confidence: 99%
“…Furthermore, pH-sensitive cancer-associated phenotypes have often been attributed solely to the effects of pHe [ 72 , 73 ], despite pHi dysregulation being a key driver of altered pHe [ 74 ]. For example, transcriptional changes inside cells have been attributed to acidification of pHe [ 68 ], but that acidification was experimentally driven by inducing intracellular hypoxia, which also changes pHi [ 75 ]. These data suggest a link between extracellular and intracellular pH environments and a role for pHi as a driver of microenvironment remodeling and tumor phenotypic heterogeneity.…”
Section: Heterogeneity and Phimentioning
confidence: 99%
“…125 However, it was observed that the expression of miR-215 in prostate cancer AT1 cell line and rat model was downregulated by extracellular acidosis and represented that pH may affect the biological behavior of tumors via miRNAs. 126 Therefore, it was suggested that this miRNA family is a positive regulator of p53, and its downregulation plays a key role in MM development. 132…”
Section: Prostate Cancermentioning
confidence: 99%